Politically Connected Firms - Faccio, Mara (American Economic Review, 2006)
Examination of firms in 47 countries shows a widespread overlap of controlling shareholders and top officers who are connected with national parliaments or governments, particularly in countries with higher levels of corruption, with barriers to foreign investment, and with more transparent systems. Connections are diminished when regulations set more limits on official behavior. Additionally, I show that the announcement of a new political connection results in a significant increase in value.